The Gaussian Sequence 3th Order Mod m - Francisco Regis Alves; Renata Teófilo De Sousa; Renata Vieira (Communications in Advanced Mathematical Sciences)
The work addresses the study of third-order recurrent sequences for mod m cases. Thus, some definitions aim to transform infinite sequences into finite ones. In this regard, the Fourier transform is used as a visualization technique, explored in Google Colab. The mathematical theorems presented are established to examine the patterns of these sequences and their corresponding cycles. As a future perspective, it is intended to investigate other mathematical theorems to generalize the sequences into finite groups.